Transformasi Kebijakan Kesetaraan Gender dalam Pengembangan SDM Kementerian Keuangan - Muslem Muslem (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study examines the impact of Sri Mulyani’s inclusive leadership on human resource development (HRD) in the Indonesian Ministry of Finance, with a focus on gender equality policies and employee capacity-building programs. Using a literature review method, this research analyzes relevant studies on inclusive leadership and its application in the public sector. The findings indicate that Sri Mulyani’s inclusive leadership, which emphasizes openness, accessibility, and equality, has successfully increased women's participation in leadership positions and fostered a more collaborative work environment. The gender equality policies implemented have not only increased the number of women in strategic positions but also strengthened overall organizational performance. Additionally, capacity-building programsdesigned to enhance technical and managerial skills have proven effective in improving productivity and innovationwithin the Ministry of Finance. This study concludes that Sri Mulyani’s inclusive leadership can serve as a model for other public sector organizations, both in Indonesia and internationally, to promote gender equality and enhance organizational performance through inclusive HR development.